2019
DOI: 10.1101/638031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetics of cytokine receptor trafficking determine signaling and functional selectivity

Abstract: Cytokines activate downstream signaling networks via assembly of cell surface receptors, but it is unclear whether modulation of cytokine-receptor binding parameters can modify biological outcomes. We have engineered variants of IL-6 with different affinities to the gp130 receptor chain to investigate how cytokine receptor binding kinetics influence functional selectivity. Engineered IL-6 variants showed a range of signaling amplitudes, from minimal to full agonist, and induced biased signaling, with changes i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 76 publications
(84 reference statements)
5
28
0
Order By: Relevance
“…We postulated that the weak binding affinity that IL-10 exhibits for IL-10Rβ critically contributed to its functional fitness, by limiting the range of concentrations at which IL-10 elicits its full immunomodulatory potential. Here, we engineered variants of IL-10 with enhanced affinity for IL-10Rβ to investigate whether the stability of the IL- reported that IL-6, another STAT3 activating cytokine, promotes strong STAT3 binding to chromatin but poor gene expression (30). Our study was done in resting monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We postulated that the weak binding affinity that IL-10 exhibits for IL-10Rβ critically contributed to its functional fitness, by limiting the range of concentrations at which IL-10 elicits its full immunomodulatory potential. Here, we engineered variants of IL-10 with enhanced affinity for IL-10Rβ to investigate whether the stability of the IL- reported that IL-6, another STAT3 activating cytokine, promotes strong STAT3 binding to chromatin but poor gene expression (30). Our study was done in resting monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Overall these observations suggest that in addition to receptor binding affinity, the stoichiometry of the IL-10-receptor complex helps to fine-tune IL-10 bioactivity potencies. We showed that the number of phospho-tyrosines available in cytokine receptor intracellular domains critically contributes to defining signalling identity by cytokines (30). IL-6 variants that triggered partial phosphorylation of Tyr residues available in the gp130 intracellular domain exhibited a biased STAT3 versus STAT1 activation (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations